Convex optimisation-based joint channel and power allocation scheme for orthogonal frequency division multiple access networks - Liu, Peng; Li, Jiandong; Li, Hongyan; Meng, Yun (IET communications, 2015)
This study concerns joint channel and power allocation scheme for multi-user orthogonal frequency division multiple access system. The author's highlight is margin adaptive (MA) resource allocation problem namely minimising the total transmit power of users with rate requirement constraints. MA is generally provable NP-hard; the typical methods are either to relax and round, or to fix the transmission mode of users (e.g. modulation and coding). Differently, they reorganise MA problem with only power variables left and design a novel relaxation scheme to enable the convexity. The polynomial-time algorithm-interior-point method-is employed to solve the relaxation problem and the theoretical complexity is further presented. Simulation results demonstrate that the author's scheme can provide high energy efficiency compared with the existing methods, 100% relative error bounds with respect to the optimum in most cases, and low computational complexity.